Dowling-Degos disease with follicular involvement associated with hidradenitis suppurativa: A manifestation of follicular occlusion phenomenon? - Bhagyashree Babanrao Supekar; Kinjal Deepak Rambhia; Rajesh Pratap Singh; Jayesh Ishwardas Mukhi (Wolters Kluwer Medknow Publications, 2020)
A 30-year-old female patient presented with progressive reticulate pigmentation of the neck, upper chest, back, cubital fossa, and axillae since the age of 15 years. The patient also complained of recurrent multiple tender nodules and plaques associated with sinuses and pus discharge over the axillae, groins, and buttocks which healed with scarring for 4 years. There were multiple pitted scars and hyperpigmented macules over the perioral area and cheeks. Scattered comedo-like lesions were present over the upper back, chest, cubital fossae, and buttocks. Histopathology from the pigmented lesion revealed thinning of the suprapapillary epidermis, epidermal hyperplasia with finger-like elongation of the rete ridges, and increased pigmentation of their lower part, suggestive of Dowling-Degos disease (DDD). Biopsy section from comedonal lesion showed dilated infundibulum and antler-like rete ridges suggestive of follicular DDD. We report a case of DDD with follicular involvement and hidradenitis suppurativa (HS) which is a rare association and can be explained on the basis of single underlying defect in follicular epithelial proliferation. DDD-HS has been shown to result from mutations in PSENEN, encoding a critical component of the γ-secretase complex.